Development of Sugar Products From Aren (Arenga Pinnata Merr) on Customer Satisfaction Using The Method with Kano (Case Study of Home Industry in Kabangka Village Kabangka District Muna Regency - Zainul Karim; Muhammad Syukri Sadimantara; Sakir Sakir (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2020)
This study aims to determine the attributes that need to be improved, maintained, and repaired to suit the needs of consumers and to determine the level of satisfaction and dissatisfaction of the Nur Mizan household industry and sugar consumers in Kabangka Village, Kabangka District, Muna Regency. The data was collected by using a literature study method, questionnaire, interview, observation, and documentation. The results of the analysis of the Kano method showed that the Must-be category, namely attributes that need to be improved, including the product brand and the design of the ant sugar packaging, including a picture of sugar palm. One-Dimensional category, namely the attributes maintained that the texture of the ant sugar is not hard, the taste of the ant sugar is quite sweet, the sugar dissolves easily when brewed with water, the distinctive aroma of ant sugar is very strong, the ant sugar is yellowish-brown, a slightly bitter taste appears in the sugar, packaging for ant sugar includes information on the composition of raw materials, packaging for ant sugar includes information on net weight, packaging for ant sugar includes information on the benefits of the product and sugar for ants has a lower price than other products. Attractive category, an attribute that needs to be improved is promotional media using Instagram, Facebook, WhatsApp, Line, and Youtube. Furthermore, the level of satisfaction (better) and dissatisfaction (worse) is measured using the Kano diagram with an average better coefficient value of 0.71 and an average score of the worse coefficient of -0.4, a better average value of 0.38 - 0.88. The average score for the worse was between -0.27 - 0.64.